The enhanced effect of tetrahydrocurcumin on radiosensitivity of glioma cells. (1st March 2018) - Zhang, Xingzhen; Peng, Lei; Liu, Anchang; Ji, Jianbo; Zhao, Lixia; Zhai, Guangxi
Abstract: Objectives: To evaluate the effects of tetrahydrocurcumin (THC) on the radiosensitivity of glioma cells and the possible molecular mechanism. Methods: MTT assay, colony forming and wound healing assays were performed to detect the proliferation, radiosensitivity and migration of cells with various treatments. Cell apoptosis, cell cycle and GHS level were determined for exploring potent sensitization mechanism of THC. Meanwhile, protein expressions of cyclin D1 and PCNA were also measured. Furthermore, both orthotopic C6 mouse models and C6 subcutaneously grafted mouse models were established to test the tumour inhibitory effects of combined treatment in vivo . Key findings: Cells treated with combined THC and radiation demonstrated lower cell viability and higher apoptosis rate as compared to radiation group. Moreover, the intracellular GSH was also decreased in the THC co-treated C6 cells. More importantly, combinatorial treatment group significantly induced G0/G1 cell cycle arrest and a decrease in the S phase cell through the down-regulation of cyclin D1 and PCNA. The in-vivo therapeutic efficacy assay indicated that the growth of tumour was greatly inhibited in combinatorial group. Conclusions: Tetrahydrocurcumin can synergistically enhance the radiosensitivity of glioma cells by inhibiting the expressions of cyclin D1 and PCNA.